Control, power, and responsibility: a qualitative study of local perspectives on problem drinking in Peruvian Andean highlands - Sakiko Yamaguchi; Raphael Lencucha; Thomas G. Brown (BMC, 2021)
Abstract Background Alcohol control has emerged as an important global health challenge due to the expanding influence of alcohol companies and limited control measures imposed by governments. In the Peruvian Andean highland, the ritual function of collective drinking is reported to have been weakened in response to the increased availability of alcohol and the experience of political violence. This study seeks to merge the broader political economy with local experience and culture to provide a deeper understanding of the dynamic between global processes and local realities. Methods We used purposive sampling to recruit participants. We conducted in-depth interviews (n = 28) and focus group discussions (n = 19) with community participants, teachers, health workers, alcohol vendors and police officers. Thematic analysis identified patterns of individual and collective meaning situated in relation to social, political and economic factors. Results Local perspectives and behaviour regarding loss of control over alcohol are shaped through the complex patterns of power and meaning exerted and experienced by different actors. Participants' emphasis on parents' lack of control over alcohol use by "abandoned" children reflects the structural vulnerability of some Andean families struggling with economic hardships. Participants also emphasized how alcohol consumption was tied to forms of control exerted by men in households. Participants expressed that some men demonstrated their masculine identity and symbolic power as the breadwinner through spending on alcohol. The third emphasis was tied to the market economy. Participants expressed that the expansion of the alcohol market and perceived absence of government control coupled with macroeconomic conditions, like poverty, shaped patterns of alcohol consumption. Conclusion Our findings illustrate how problem drinking is shaped not simply by an individual drinker's lack of self-control but also by a regulatory environment that enables the unrestrained marketing of alcohol products and the creation of a culture of consumption. Harmful consumption is mediated by the reshaping of the Andean cultural practice of collective drinking. Attending to local perspectives is essential for policies and interventions that connect structural dynamics with the cultural and experiential aspects of alcohol consumption.